A new integrated approach to cardiac mechanics: reference values for normal left ventricle - Faganello, Giorgio; Collia, Dario; Furlotti, Stefano; Pagura, Linda; Zaccari, Michele; Pedrizzetti, Gianni; Di Lenarda, Andrea (International journal of cardiac imaging, 2020)
The association between left ventricular (LV) myocardial deformation and hemodynamic forces is still mostly unexplored. The normative values and the effects of demographic and technical factors on hemodynamic forces are not known. The authors studied the association between LV myocardial deformation and hemodynamic forces in a large cohort of healthy volunteers. One-hundred seventy-six consecutive subjects (age range, 16–82; 51% women), with no cardiovascular risk factors or any relevant diseases, were enrolled. All subjects underwent an echo-Doppler examination. Both 2D global myocardial and endocardial longitudinal strain (GLS), circumferential strain (GCS), and the hemodynamic forces were measured with new software that enabled to calculate all these values and parameters from the three apical views. Higher LV mass index and larger LV volumes were found in males compared to females (85 ± 17 vs 74 ± 15 g/m 2 and 127 ± 28 vs 85 ± 18 ml, p < 0.0001 respectively) while no differences of the mean values of endocardial and myocardial GLS and of myocardial GCS were found (p = ns) and higher endocardial GCS in women (− 30.6 ± 4.2 vs − 31.8 ± 3.7; p = 0.05). LV longitudinal force, LV systolic longitudinal force and LV impulse were higher in men (16.2 ± 5.3 vs 13.2 ± 3.6; 25.1 ± 7.9 vs 19.4 ± 5.6 and 20.4 ± 7 vs 16.6 ± 5.2, p < 0.0001, respectively). A weak but statistically significant decline with age (p < 0.0001) was also found for these force parameters. This new integrated approach could differentiate normality from pathology by providing average deformation values and hemodynamic forces parameters, differentiated by age and gender.